TRANSNATIONAL FRONT OF THE CAUCASUS POLITICAL EMIGRATION, WESTERN VALUES (1952–1955) - Enver Diasamidze (International Journal of Innovative Technologies in Social Science, 2025)
The years 1952–1955 are one of the most important stages in the history of Caucasian political emigration. It was during this period, on the basis of high-level conferences held in Paris, that an anti-Soviet transnational political front was formed, based on democratic values, national self-determination, and cooperation based on regional equality. The movement aimed not only to fight against the Soviet regime, but also to create a new political architecture for the Caucasus region based on a federal or confederal model. The article draws on archival documents and American strategic materials from the Cold War period and provides an interdisciplinary analysis of both documentary sources and the ideological content of the discourse.The main focus is on the "Union Council" and "Working Committee" created by the Paris conferences, which prepared the institutional form of Caucasian unity. The text also reflects on the relations with Western institutions (ACEN, Crusade for Freedom) with the aim of bringing the Caucasian anti-Bolshevik movement into the framework of the global democratic discourse.Special emphasis is placed on the fact that political emigration actors did not identify with aggressive nationalism, but rather supported multi-ethnic coexistence, a legal framework, and Western civilized values. The study shows that the formation of the anti-Bolshevik front in the Caucasus was one of the first transnational attempts to achieve regional security, sovereignty, and democratic institutionalization.